P107 Socio-cultural factors influencing condom use intentions among African migrant youth in South Africa. (14th July 2019) - Titus, Raylene Rozita; John-Langba, Johannes
Abstract : Background: Although the condom use behaviours among youth in South Africa has been studied extensivly, very little in known about the socio-cultural factors that influence intentions to use condoms during sexual intercourse among young people generally and African migrant youth in particular. This study utilized the theory of planned behavior to explore socio-cultural factors that influence condom use intentions among African migrant youth in South Africa. Methods: Using a qualitative research approach and snow-ball sampling procedures, indepth interviews were conducted with 20 migrant youth from other African countries, aged between 20-25 years and residing In Cape Town, South Africa. Results: Most African migrant youth residing in South Africa have acceptable levels of knowledge about condoms and condom use and linkages to HIV prevention and safer sexual practices. Traditional norms on sexual behaviour prohibit young migrants to freely discuss safer sexual choices. Gendered norms in sexual relationships, acculturation and cultural expectations of referent others reportedly influence intentions to use condom during sexual intercourse. Conclusion: The nexus among socio-cultural norms, acculturation and safer sexual choices are shown to be crucial to any HIV prevention interventions among African migrant youth in South Africa. Disclosure: No significant relationships.